Parasites Between the Ancient China and Western Culture - Tornali, Cristina; Vecchio, Ignazio; Kuvačic, Goran; Vecchio, Flavio Alfio Giangiuseppe; Angilletta, Sonia; De Giorgio, Andrea (Medicina Historica, 2023)
Ancient Chinese documents of the II century BC were written in regarding to first parasites that can afflict the health of human beings. During the Chinese Sui dynasty, Ch’ao-Yuan-Fang, author of a book on the etiology of diseases, entitled Ch’ao-Scih-Ping-Yuan, described for the first time nine worms, responsible for numerous diseases: Fu-Ch’ung (hidden worm); Yu-Ch’ung (long worm); Pai-Ch’ung (white worm); Jao-Ch’ung (fleshy worm); Fei-Ch’ung (lung worm); Wei-Ch’ung (stomach worm); Jom- Ch’ung (weak worm); Ch’ih-Ch’ung (red worm); Jao-Ch’ung (writhing worm). As for other human parasites, the Far East he was struggling with fleas, bugs, ticks and lice, for which the Chinese used cinnabar smoke, the peach tree extract was used against the fleas. In the history of medicine, and in particular in the field of contagious diseases, ancient China preceded by centuries the Western knowledge. The ancient Chinese understood that some diseases were contagious and had observed, for example, that those who had contracted smallpox, healing, were no longer infected, so they adopted the system to infect healthy children in order to cause the disease in them.